Characterization of Hydrochar Produced by Hydrothermal Carbonization of Organic Sludge. Issue 1 (28th December 2020) - Wang, Wei; Chen, Wen-Hua; Jang, Ming-Feng
Sludge is a serious problem due to the risks to environment. Therefore, an energy-efficient, economic-feasible and environmental sustainable measure for sludge management is urgently required, while hydrothermal carbonization (HTC) has been regarded as one promising method. In this study hydrothermal carbonization was utilized to convert organic sludge (OS) into solid carbonaceous product (hydrochar) under various reaction temperature (T = 180–240 °C) and residence time (t = 60–240 min), respectively. The reaction pressure ranged from 2.7 to 4.8MPa, depending on the reaction conditions. The obtained hydrochar was analyzed by elemental analysis, proximate analysis, SEM, FTIR, and BET, to investigate the effect of reaction parameters on the hydrochar properties, followed by discussions on potential applications of the obtained hydrochar. Obvious reduction of H/C and O/C ratio after HTC was observed, based on the Van Krevelen diagram and FTIR analysis, revealing that the dehydration and decarboxylation occurred during the HTC process. The reaction temperature was regarded as the dominant parameter affecting hydrochar characteristic, compared to residence time. The severity factor (log Ro ) at the range from 4.13 to 5.90 showed good linear relationship with the ash content, volatile matter (VM), N content and H/C ratio of hydrochar, indicating that the severity factor could serve as a useful indicator for analyzing the hydrochar property. Although the surface area and porosity were improved by HTC, subsequent modification and activation should be needed to broaden the application field. Owing to the characteristic of high ash content, hydrochar derived from organic sludge might not be feasible for fuel use. Instead, the precursor of the activated carbon and low-cost adsorbent might be the potential applications, while further works should be needed to verify the feasibility.